Collaboration in nursing-home care: perspectives of care professionals – a qualitative study - Anke Persoon; Marleen H Lovink; Roeyel J F Koldeweij (BMJ Open Quality)
Interprofessional collaboration became more firmly positioned after the WHO highlighted its importance for better healthcare outcomes. In nursing homes, interprofessional collaboration refers to collaboration between teams of physicians/allied health professionals and care teams. Collaboration within care teams is known as intraprofessional collaboration. Determinants of interprofessional and intraprofessional collaboration have yet to be explored within the nursing-home context. Our exploratory qualitative study focused on the determinants considered important by professionals in seven nursing homes. We conducted 14 one-on-one, semistructured interviews with nurses and collaborating physicians/allied health professionals from seven teams of one care organisation. Data were analysed on thematic analysis, proceeding from an inductive approach. Five interacting determinants were identified. The core determinant was ‘investing in each other’, followed by ‘roles, functions and responsibilities within care teams’; ‘written policies for individual residents’; ‘verbal coordination meetings’; and ‘organisational influences’. One notable finding is the influence of intraprofessional collaboration within the care team on all determinants of interprofessional collaboration, including the role of the coordinating nurse. Future ethnographic and action research on intraprofessional collaboration is needed, including the perspective of nurse assistants, as well as on interventions aimed at improving interprofessional collaboration. We recommend training professionals to invest in each other as a skill that encourages relationships.